Determination of benzimidazole pesticide residues in soil by ultrasound‐assisted supramolecular solvent microextraction. Issue 4 (17th February 2023) - Hu, Jiabao; Yang, Yuqi; Guan, Yunlei; Li, Rui; Liu, Chunxiao; Yao, Guojun; Zhao, Wenting
Abstract: The objective of this study was to develop a simple, rapid, and efficient pretreatment method using a supramolecular solvent as the extractant combined with high‐performance liquid chromatography‐ultraviolet to detect benzimidazole residues in environmental soil. The supramolecular solvent was composed of long‐chain alcohols, tetrahydrofuran, and water in proportion, showing excellent solubility and polarity range, so a supramolecular solvent microextraction method was established. The optimum method was identified by optimizing the types of long‐chain alcohols, the alcohol/tetrahydrofuran ratio, the pH, the amount of extractant, and the extraction time. The detection limits were 12.1–39.9 μg/kg with a relative standard deviation between 1.2% and 3.2% ( n  = 6). The recoveries ranged between 56.6% and 86.1%, and the linear relationship was good. The correlation coefficient (r 2 ) was 0.9843 ‐ 0.9998. This method was then used to measure five benzimidazoles (thiabendazole, albendazole sulfone, ophendazole, albendazole, and fendazole) in soil samples.